Generation of Bacterial Diversity by Segregation of DNA Strands - Norris, Vic; Ripoll, Camille (Frontiers in Microbiology, 2021)
The generation in a bacterial population of a diversity that is coherent with present and future environments is a fundamental problem. Here, we use modeling to investigate growth rate diversity. We show that the combination of (1) association of extended assemblies of macromolecules with the DNA strands and (2) the segregation of DNA strands during cell division allows cells to generate different patterns of growth rate diversity with little effect on the overall growth rate of the population and thereby constitutes an example of ‘order for free’ on which evolution can act.